Avaliação da influência da carbonatação e do ensaio de envelhecimento acelerado por ciclagem térmica em argamassas de revestimento - Silva, Kétlin Gabriele Cornely da (Universidade do Vale do Rio dos Sinos, 2022)
The effects of exposure conditions of coating mortars are crucial factors when it comes to their durability, therefore, the present work aims to evaluate the effects caused by carbonation and accelerated aging on the mechanical properties of this material. To carry out the experimental program, specimens composed of smooth structural ceramic substrates coated with cement mortar, lime and sand with a 1:1,5:4 ratio and a water/binder ratio of 0,9 were made, which were cured in a saturated enviroment for 61 days. After curing, the cladding boards that were to be aged and carbonated were subjected to aging at a controlled humidity of 60% ± 5% for 25 days. Subsequently, half of the samples were subjected to accelerated carbonation with a concentration of 3% CO2 and the others were subjected to the accelerated aging test. Accelerated aging occurred in carbonated and non carbonated samples over 10 heating and wetting cycles. The samples of each variable were analyzed from the tensile bond strength tests, capillary water absorption and tensile test with the application of the Digital Image Correlation (DIC) methodology, which aims to map the deformations and perform the analysis visually. The results show that carbonation contributed to greater resistance and lower capillary absorption, but when the sample was aged, it generated a loss of resistance. The accelerated aging test contributed to a gain in strength in the non carbonated samples. Aging also generated greater variability in the tensile bond strength and water absorption tests. The analysis of strains by DIC confirmed the results obtained in the tensile bond strength test, proving that the method is valid.
Keywords: Argamassas de revestimento; Carbonatação; Digital Image Correlation (DIC); Envelhecimento acelerado; Accelerated aging; Carbonation; Coating mortars